Students’ Perception of Online Learning in English Subject at SMK Negeri 3 Karang Baru - Siska Nanda Dewi (JADEs Journal of Academia in English Education, 2022)
This study aimed to determine students' perceptions of online learning English at SMK Negeri 3 Karang Baru. This study used a qualitative method. The researcher used questionnaire as the instrument of research. In this study, the researcher found that many students did not agree with online learning. The material was difficult to understand, it was constrained by internet signals, so they preferred to study as usual. Based on the explanation above, it can be concluded that students' perceptions of online learning English were negative, and they were not satisfied with online learning English.